80 Years of Aerospace Engineering Education in the Netherlands - Saunders-Smits, Gillian (TU Delft Open, 2020)
This year, 2020, the Faculty of Aerospace Engineering at Delft University of Technology in the Netherlands celebrates its 80th birthday. This paper describes the history of the department since its founding in early 1940, just before the start of World War II in the Netherlands, until present day. The paper will highlight how its research and education developed within the socio-economic context of the Netherlands and the developments in aerospace over the past 80 years.